Implementation of proportional integral derivative (PID) controller on coupled tank liquid system - Saiful Norazwan , Mohd Ariffin (2008)
Nowadays, the liquid level control is one most important element in industrial field especially in chemical industry. The basic concept of how the coupled tanks system work in this project is by using computer as the main control where user can control the level of liquid in one tank or both tanks. The purpose of this project is to implement PID controller on coupled tank liquid level system by using visual basic software. The visual basic software are used because it easy to interface with hardware. PID controller was used due to widely acceptance applicability in process industry. The mathematical model of PID controller was used implement as such to produces suitable output so that the liquid level can be controlled at desired set point. Meanwhile, the mathematical model of coupled tank liquid level system was derived to obtain the transfer function of the plant and later be used to simulate the plant performance in MATLAB program.